Impact of surgical restaging on recurrence in patients with borderline ovarian tumors: A meta-analysis. (May 2020) - Chevrot, A.; Héquet, D.; Fauconnier, A.; Huchon, C.
Abstract: Objective: The benefits of restaging surgery for patients with a borderline ovarian tumor (BOT) discovered on initial surgery are debatable. We performed a meta-analysis to evaluate the role of restaging surgery on recurrence in patients with BOTs. Study design: We systematically reviewed published studies comparing restaging surgery and incomplete surgery in BOT patients from January 1985 to December 2017. Endpoints were recurrence and mortality rates. Study design features that possibly affected participant selection, reporting of recurrence and death, and manuscript publication were assessed. For pooled estimates of the effect of restaging surgery on recurrence, fixed-effect meta-analytical models were used. Results: Of the 577 articles initially selected, four retrospective observational studies (Restaging group: 166 patients; Non-Restaging group: 394 patients) met our research criteria. No significant differences in terms of recurrence between the two groups were observed (pooled Peto Odds Ratio [OR] = 0.88; 95 % confidence interval [CI]: 0.41–1.92). The number of deaths was insufficient for statistical analysis. Conclusions: This meta-analysis based on retrospective studies, suggests that restaging surgery does not significantly reduce recurrence in patients with BOT.